1976
DOI: 10.1159/000231701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of K-Cell Activity by Use of Depletion Experiments

Abstract: Normal human blood lymphocytes with affinity for ox red cells sensitized with IgG antibody, for normal or papain-treated sheep red cells and for ox red cells coated with mouse complement were used for rosette formation and the rosetting cells separated by density gradient centrifugation on Ficoll/Hypaque. The non-rosetting cells at the interface were collected and compared with cell suspensions before treatment for direct and antibody-dependent cytotoxicity of human target cells. Depletion of Fc-receptor-beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In rodents, various T lymphocyte depletion procedures failed to modify K cell activity [Harding et ai, 1971;Van Boxel et al, 1972], Similarly, in man, depletion of T lymphocytes did not reduce K cell activity [Wisloff et al, 1974;De Bracco et al, 1976;Hersey et al, 1976;Kraft et al, 1976]; enrichment of T lymphocytes pro duced no change or a reduction of K cell ac tivity [De Bracco et al, 1976;Cordier et al, 1976;Hersey et al, 1976], Our present studies confirmed these findings. That a more obvious augmentation of K cell activity was not always observed (e .g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In rodents, various T lymphocyte depletion procedures failed to modify K cell activity [Harding et ai, 1971;Van Boxel et al, 1972], Similarly, in man, depletion of T lymphocytes did not reduce K cell activity [Wisloff et al, 1974;De Bracco et al, 1976;Hersey et al, 1976;Kraft et al, 1976]; enrichment of T lymphocytes pro duced no change or a reduction of K cell ac tivity [De Bracco et al, 1976;Cordier et al, 1976;Hersey et al, 1976], Our present studies confirmed these findings. That a more obvious augmentation of K cell activity was not always observed (e .g.…”
Section: Discussionmentioning
confidence: 99%
“…In man, several studies have shown, that re moval of these cells on FicoII gradients pro duced no change in ADCC [De Bracco et al, 1976;Hcrsey et al, 1976;Kraft et al, 1976], but both Peter et al [1975] and Cordier et al [1976] found a reduction in ADCC. The latter, however, noted a mini mal change of K cell activity following their removal on a nylon column.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using rosetting reactions to deplete and enrich specific lymphocyte subpopulations, Coombs and his colleagues were then able to test the various fractions obtained for their cytotoxicity against leucocytes sensitised with HLA antibody. They found that depletion of Fc -bearing cells reduced antibody-dependent cellular cytotoxicity (ADCC) suggesting that cytotoxic K cells had Fc receptors (Kraft et al, 1976). In a subsequent report they concluded that the PB NK cell was a non -T, Ig positive, Fc positive and complement receptor negative cell.…”
Section: Investigation Of Lymphocyte Subpopulationsmentioning
confidence: 99%